(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2025)
This paper examines Georgia O’Keeffe’s ‘My Last Door’ through the lenses of compositional interpretation, semiotics, and discourse analysis. Created during a period of war, fascism and social upheaval, the painting interrogates societal structures while reflecting the individual’s precarious position within them. ‘My Last Door’ encapsulates the emotional and psychological landscape of mid-20th-century America, employing geometric simplicity and a muted colour palette to convey themes of loss, transition, and constrained identity. Utilising Saussure’s theory of signs, Barthes’ concepts of denotation and connotation, and Foucault’s discourse on subjectivity, this analysis uncovers the layered meanings embedded in O’Keeffe’s visual language. Additionally, a feminist reading positions the painting as an assertion of autonomy within a male-dominated artistic tradition. Ultimately, ‘My Last Door’ invites viewers to engage in a process of deconstruction, challenging fixed interpretations and opening pathways for new creative and existential possibilities.